Study analysis on destination priority ranking using AHP technique for Malaysia’s investment on bullet train / Huzalina Hussin, Norliza Abdullah and Nor Sakinah Abd Eanich - Hussin, Huzalina; Abdullah, Norliza; Abd Eanich, Nor Sakinah (2013)
Bullet Train is currently regarded as one of the most significant technological breakthroughs in passenger transportation. In Malaysia, there is a proposal to build bullet-train as an alternative mode of transportation. Malaysia government is in the process of evaluating and there is no decision has been recorded thus far. This study intent is to evaluate where is the most potential market to build Bullet Train in Malaysia for sustainable and profitable services. As the cost of building the high speed rail system or bullet train is very high and very risky for taxpayers and private investors, it is beneficial to learn from empirical data, historical trends and international experiences. Thus the objective of this study is to identify criteria and suggest the priority ranking among 3 selected pair destinations by using Analytical Hierarchy Process (AHP) calculation. The selected destinations are Kuala Lumpur to Johor Bahru, Kuala Lumpur to Kuantan and Kuala Lumpur to Pulau Pinang. Whereas, the selected criteria are population, distance, economic development, congestion and surrounding areas. Finding shows that the best destination is Kuala Lumpur to Pulau Pinang followed by Kuala Lumpur to Johor Bahru and Kuala Lumpur to Kuantan. Moreover, the most important criteria that contribute to the chosen destination is congestion, compared to population, economic development, distance and surrounding areas.